ANALISIS DETERMINASI FRAUD DIAMOND DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN - Adam Maulana Prastyo; Aris Eddy Sarwono; Dewi Saptantinah Puji Astuti (JURNAL ILMIAH EDUNOMIKA, 2023)
The purpose of this study is to determine the influence of diamond fraud elements consisting of pressure elements (which are proxied with financial stability, external pressure, and financial targets), oppoturnity elements that are proxied by ineffective monitoring, rationalization elements that are proxied by change on auditors, and capability elements that are proxied by change in director against financial statement fraud in banking sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The samples used in this study were 34 companies with purposive sampling method. The analysis method in this study is multiple linear regression. The results showed that financial stability, change on auditors, and change in directors had a significant positive effect on financial statement fraud. Meanwhile, external pressure, financial targets, and ineffectibe monitoring do not have a significant influence on financial statement fraud.